Rethinking political attitudes of migrants from Turkey and their Germany-born children : beyond loyalty and democratic culture - Adar, Sinem (2019)
Zusammenfassung: Since the presidential elections in 2014, Turkish voters abroad have cast their votes in three parliamentary elections, one presidential election, and one referendum. The relatively higher vote share that the Justice and Development Party (AKP) and President Recep Tayyip Erdoğan garnered in Germany and other European states with large Turkish immigration levels, such as the Netherlands, Belgium, and Austria, has remained a cause for concern to politicians and the public in these countries. Especially in Germany, the dominant premise in the public debate has been that voting in favor of the AKP and Erdoğan is a sign of "loyalty to Turkey" and an absence of a commitment to democratic values and norms. The broad appeal that the AKP and Erdoğan have among migrants from Turkey and their children has both a material and an emotional basis. Socio-economic changes and perceived improvements in the quality of state institutions, both within Turkey and Germany, seem to have created a positive image of the party. In addition, a strong sense of pride arising out of the perception of a "strong Turkey" under the leadership of President Erdoğan seems to drive electoral support. Finally, a fear of losing social and political gains also facilitates electoral support for the AKP. Given that the interest of the Turkish government in the migrant population is driven by its foreign- and domestic-policy ambitions, it is likely to continue in the future with a strong identitarian focus. Moreover, Turkey’s deepening economic crisis is also likely to accentuate the need for economic remittances. It is vitally important to differentiate between the Turkish government’s systematic efforts to instrumentalize migrants and their foreign-born children toward its domestic- and foreign-policy ends and the demands of migrants for political representation and equal recognition